The Powerful Numbers? - Krause, Ulrike (Migration and society : advances in research, 2022)
The Global Trends Reports represent UNHCR's key tool to share information about annual developments in relation to displacement, primarily through numbers. Among the many subjects covered, they often also address different forms of accommodation. But how do such quantifications produce (non)knowledge and link with the humanitarian landscape? This article explores accommodation categories, quantifications, and local categorizations as presented in the Global Trends Reports published from about 2003 to 2020. While the numbers appear to display precise knowledge on refugees' whereabouts, gaps prevail in the reports: accommodation categories remain undefined, calculations are partly unclear, and local recategorizations occur suddenly without explanation. This article argues that these issues produce nonknowledge, and that the reports' continuous attention to accommodation data simulates refugees' controllability and governability. * KEYWORDS: accommodations, (non)knowledge, quantification, refugees, UNHCR